PTU-040 Five Year Outcomes For Patients Undergoing Endoscopic Therapy For Barrett's Related Neoplasia From The United Kingdom's Largest Single Centre Experience. (9th June 2014) - Haidry, RJ; Banks, M; Gupta, A; Butt, M; Rodriguez-Justo, M; Novelli, M; Lovat, L
Abstract : Introduction: The National Institute of Clinical Excellence (NICE) in the United Kingdom (UK) approved the use of Radiofrequency ablation (RFA) as minimally invasive endoscopic therapy for the treatment of Barrett's Oesophagus related neoplasia as an alternative to surgery in 2010. These high risk patients carry a 40–60% risk of progressing to Osophageal Adenocarcinoma (OAC), survival from which is poor. Over the past 5 years combined endoscopic mucosal resection (EMR) and RFA have become the preferred intervention for the curative treatment of patients with BE related neoplasia. Methods: We report prospective data from one of the UK's largest academic tertiary centres for patients undergoing RFA for early neoplasia arising in BE between 2008–2013 at University College Hospital, London. Before RFA, visible lesions were removed by EMR. Patients then underwent RFA every 3 months until all visible BE was ablated or cancer developed (endpoints). Biopsies were taken at 12 months or when endpoints reached. Primary outcomes were clearance for dysplasia (CR-D) and BE and intestinal metaplasia (CR-IM) at 12 months. Long term durability for CR-D for those with favourable outcomes at 12 months was assessed. Results: Two hundred patients have undergone RFA since 2007 at our centre. Of these 145 have completed treatment. Most are male (83%), mean age 69 years (range 44–91). Baseline histology HGD in 86% and IMC in 14%. Mean length BE segment prior to RFA 6cm (range 1–20). Ten per cent patients in our cohort underwent RFA for residual neoplasia after unsuccessful Photodynamic therapy (PDT). Prior to RFA treatment, 50% of patients had EMR for visible lesions. After 2–3 RFA treatments (range 1–6) over 12 months, 80% (116/45) patients had achieved CR-D and 65% CR-IM (94/145). Pre-treatment PDT, EMR or histology did not influence outcomes. Three patients (2.5%) progressed to invasive OAC at 12 months and in total 8 (7%) progressed at most recent follow up. At 5 years 95% of patients who had dysplasia clearance at 12 months remain disease free (median follow up 20 months, IQR 9–32). Kaplan Meir survival statistics demonstrate at 5 years after successful treatment 75% and 77% of patients are likely to remain free of dysplasia and IM respectively. Conclusion: We report on the UK's single largest prospective series to date of patients undergoing endoscopic therapy for BE related neoplasia. Our outcomes compare favourably with those published around the world and from within the UK patient registry. These patients are high risk and require vigilant follow up even after successful treatment as predicted recurrence can occur in up to 25% of cases. Disclosure of Interest: None Declared.